QR Code Mobile sebagai Pendukung Rekam Medik Berkas Rawat Jalan RS. St. Elisabeth Semarang - Aldhi Ari Kurniawan; Danang Wahyu Utomo (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Medical record play important role in order to improve hospital healthcare quality. Medical record must provide proper, fast, and relevant data. Current medical records documentation is manual based in mean the documents are available in notes and document maps. There is no integration among the document, and it can caused a misunderstanding among hospital stakeholder such as doctor or nurse and also duplicated data. QR code is one of alternative to handle completeness file, searching document, and store all document. The combination between QR code, web and mobile platform can handle the problem faced by hospital stakeholder. In testing phase, the proposed system can handle medical record problem in RS. St. Elisabeth. Average of respondent, more than 50% state that sistem is good to handle tracking record, completeness file, and store.